Development and In Vivo Application of a Water-Soluble Anticancer Copper Ionophore System Using a Temperature-Sensitive Liposome Formulation - Anikó Gaál; Tamás M. Garay; Ildikó Horváth; Domokos Máthé; Dávid Szöllősi; Dániel S. Veres; Jeremiah Mbuotidem; Tibor Kovács; József Tóvári; Ralf Bergmann; Christina Streli; Gergely Szakács; et al. (MDPI AG, 2020)
Liposomes containing copper and the copper ionophore neocuproine were prepared and characterized for in vitro and in vivo anticancer activity. Thermosensitive PEGylated liposomes were prepared with different molar ratios of 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) and hydrogenated soybean phosphatidylcholine (HSPC) in the presence of copper(II) ions. Optimal, temperature dependent drug release was obtained at 70:30 DPPC to HSPC weight ratio. Neocuproine (applied at 0.2 mol to 1 mol phospholipid) was encapsulated through a pH gradient while using unbuffered solution at pH 4.5 inside the liposomes, and 100 mM HEPES buffer pH 7.8 outside the liposomes. Copper ions were present in excess, yielding 0.5 mM copper-(neocuproine)2 complex and 0.5 mM free copper. Pre-heating to 45 °C increased the toxicity of the heat-sensitive liposomes in short-term in vitro experiments, whereas at 72 h all investigated liposomes exhibited similar in vitro toxicity to the copper(II)-neocuproine complex (1:1 ratio). Thermosensitive liposomes were found to be more effective in reducing tumor growth in BALB/c mice engrafted with C26 cancer cells, regardless of the mild hyperthermic treatment. Copper uptake of the tumor was verified by PET/CT imaging following treatment with [64Cu]Cu-neocuproine liposomes. Taken together, our results demonstrate the feasibility of targeting a copper nanotoxin that was encapsulated in thermosensitive liposomes containing an excess of copper.